(untitled) (Tempo e Argumento, 2011)
In the early twentieth century, the ongoing social discourse was about valuing and protecting minors. In this period, a number of adults requested to be granted the guardianship of children in order to watch over their health, diet, housing and education. Guardianship was a commitment requested by a person to the Orphan Court to manage the assets and physical integrity of the minor. However, if the discourse was to take care of the minor’s well-being, why did adults opt for guardianship instead of adoption? This study addresses the issue and proposes some answers for this question.